African financial development dynamics: big time convergence. Issue 2 (2014) - Simplice A. Asongu
<x xml:space="preserve"> Abstract </x> Purpose – Assessment of African financial development dynamic convergences in money, credit, efficiency and size. The paper aims to discuss these issues.Design/methodology/approach – The empirical evidence is premised on 11 homogenous panels based on regions (Sub‐Saharan and North Africa), income‐levels (low, middle, lower‐middle and upper‐middle), legal‐origins (English common‐law and French civil‐law) and religious dominations (Christianity and Islam). The paper examines convergence in financial intermediary dynamics of depth, efficiency, activity and size. Findings – Findings suggest that countries with small‐sized financial intermediary depth, efficiency, activity and size are catching‐up countries with large‐sized financial intermediary depth, efficiency, activity and size, respectively. The paper also provide the speeds of convergence and time necessary to achieve a full (100 percent) convergence. Practical implications – The presence of strong links among African banking sectors may present little opportunity for portfolio diversification. The convergence patterns show positive steps toward regional integration. As a policy implication, African governments should not relent in structural and institutional reforms. Originality/value – It is the first critical assessment of convergence in financial intermediary development dynamics in the African continent. <ack> <x xml:space="preserve"> Acknowledgements </x> JEL Classifications — F15, F36, F42, O55, P52 The author is highly indebted to the editor and referees for their very useful comments. </ack>